2010
DOI: 10.1017/s0950268810000439
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of asymptomatic norovirus infection in the community in England

Abstract: Existing estimates of the incidence of infectious intestinal disease (IID) caused by norovirus are based on electron microscopy or reverse transcription-polymerase chain reaction (RT-PCR). Neither method accurately represents norovirus disease burden: Electron microscopy has poor diagnostic sensitivity, and RT-PCR has poor diagnostic specificity. In this study, viral load measurements were used to identify cases of norovirus-associated IID and to produce new incidence estimates for England. IID cases were asce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
53
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 40 publications
4
53
1
Order By: Relevance
“…There is no clear animal reservoir for HuNoV, suggesting that it has other adaptations for viral maintenance between outbreaks. Asymptomatic and persistent shedding is likely to be one way that HuNoVs are maintained (4)(5)(6)(7)11), yet many questions remain about the mechanism of NoV persistence. Furthermore, while asymptomatic shedding has been demonstrated for many enteric viruses (43)(44)(45), a tractable model has not been established in which to study enteric persistence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no clear animal reservoir for HuNoV, suggesting that it has other adaptations for viral maintenance between outbreaks. Asymptomatic and persistent shedding is likely to be one way that HuNoVs are maintained (4)(5)(6)(7)11), yet many questions remain about the mechanism of NoV persistence. Furthermore, while asymptomatic shedding has been demonstrated for many enteric viruses (43)(44)(45), a tractable model has not been established in which to study enteric persistence.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence for an animal reservoir of HuNoV, suggesting that asymptomatic shedding within the human population initiates symptomatic infection. Indeed, PCR-based detection has shown that HuNoVs are present in asymptomatic individuals within a variety of communities and ranges in prevalence from 3 to 13% (4)(5)(6)(7). Furthermore, experimental infection of volunteers revealed that some individuals continue to shed virus for up to weeks after the resolution of symptoms (8), and there are examples where outbreaks likely originated with asymptomatic HuNoV shedders (9)(10)(11).…”
mentioning
confidence: 99%
“…Real-time RT-PCR testing of fecal specimens of asymptomatic individuals in England revealed a 12% age-adjusted prevalence of norovirus, with the highest prevalence noted for children Ͻ5 years of age (27). One source of asymptomatic shedding can be a recently resolved infection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper reported that the age-adjusted prevalence of asymptomatic NoV infection in England was 12%, and it displayed winter seasonality (22). Shedding in combination with inappropriate personal hygienic measures may easily lead to contamination of surfaces or food, which also applies when hands are not properly washed after staff clean bathrooms or change diapers.…”
Section: Discussionmentioning
confidence: 99%